An Uplifting Memento - Modonese, Alexander (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2020)
The following short text will explore the professional challenges faced by Mr. Davood Salimi, an Iranian immigrant who suffers from hearing, memory, and coordination issues. At Salimi’s request, the name of his medical condition will not be disclosed. The article will provide readers with a basic summary of Salimi’s biographical information, such as his professional qualifications, and explain the tragic circumstances which led to the development of his medical condition. The invaluable career assistance which AIM CROIT provided for Salimi will also be briefly discussed. In addition, the founding of this organisation and its many accomplishments will be succinctly explained. Finally, the article will conclude with a summary of Salimi’s future career goals and his advice for other individuals who suffer from disabilities.